Effects of Microgravitation on Electrofusion of Plant Cell Protoplasts - Mehrle, Werner (1989)
Electrofusion of evacuolated with vacuolated mesophyll protoplasts of Nicotiana tabacum was performed as part of the German Sounding Rocket Program (TEXUS 17, 1988). The results indicate a significant increase not only in the yield of 1:1 hybrids, but also in homo- and multifusion products. Hybrids obtained under microgravity have been shown to be viable to a higher degree with respect to their ability for light-dependent O(2)-evolution (independent of other substrates than bicarbonate). This finding is of interest for fusion experiments were only limited numbers of fusion partners are available (e.g. protoplasts from embryogenic tissues) or where fusion yields are extemely low under 1 × gravity (e.g. protoplasts of different specific density).